Addiction Services for Veterans: Opportunities in Acute Care. Issue 1 (2nd January 2023) - Shah, Meghna N.; Starks, Helene; Wander, Pandora L.; Saxon, Andrew J.
Abstract : Objective: This study aimed to estimate the proportion of total hospital discharges that involved a primary or secondary substance-related diagnosis code (SubDx) on inpatient medicine, psychiatry, and surgery services as part of a needs assessment for inpatient addiction consultation at our large, academic-affiliated Veterans Affairs (VA) hospital. Methods: We first calculated the percentage of total and service-specific discharges with a primary or secondary substance-related International Classification of Disease, Tenth Revision, code on all inpatient services (medicine, psychiatry, and surgery) in Fiscal Year 2017, 2018, and 2019, using facility-level data. Second, we calculated the proportion of total discharges that involved alcohol- and opioid-related diagnoses. Results: Over the 3 years studied, 29% of total discharges had a SubDx (4469 of 15, 575). The proportion of total discharges that involved a SubDx was 23% (1246 of 5449) in 2017, 31% (1664 of 5332) in 2018, and 33% in 2019 (1559 of 4794), a statistically significant increase ( P < 0.001). As a percentage of service-specific discharges, 65% of discharges from psychiatry (1446 of 2217) had a SubDx, compared with 25% from medicine (2469 of 9713), and 15% from surgery (554 of 3645). Medicine services had the most discharges with SubDx, with a year-over-year increase in the number of discharges with SubDx. The percentage of total discharges that involved alcohol- and opioid-related diagnoses was 14% and 4%, respectively. Conclusions: Substance-related diagnoses are prevalent at our hospital and are increasing over time. The largest number of discharges with SubDx was found on medicine services. Alcohol-related diagnoses were nearly 4 times more prevalent than opioid-related diagnoses. We found focused need around alcohol use and alcohol withdrawal.